Congenital neonatal hemochromatosis with recurrent neonatal deaths - a diagnostic nightmare: A case report (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Neonatal hemochromatosis (NH) is a rare disorder and the most common cause of acuteliver failure in neonates. NH is characterized by severe hepatic injury and iron overload with highperinatal mortality and morbidity. There is a high risk of recurrence in subsequent pregnancies of womenwho have had a child with neonatal hemochromatosis.Case presentation: A 40-year-old para 13 with one living child and three previous cesarian scarspresented at ten weeks with a history of recurrent neonatal deaths. Her last infant death was at fourmonths after she delivered a baby via cesarian birth at 36 weeks. The infant developed severe jaundicewith reduced urine output. Laboratory investigations revealed deranged liver function tests with elevatedserum ferritin levels. The infant received repeated exchange transfusions, immunoglobulin, anddexoferamine. However, she succumbed at four months. Her management for the current pregnancyrequired close follow-up and she delivered at 37 weeks gestation to a live male infant who is faring well.Discussion: The cause of NH is not fully understood. Significant evidence indicates that most cases ofneonatal hemochromatosis result from fetal liver disease due to maternal-fetal alloimmunity, a conditiontermed gestational alloimmune liver disease (GALD). In GALD, these antibodies bind to fetal liverantigen and activate the terminal complement cascade, resulting in hepatocyte injury and death.Conclusion: NH is the most common cause of neonatal acute liver injury and should be considered in allcases of severe fetal liver injury as well as in cases of stillbirth, fetal demise, and early postnatal death.